SGK1-regulated metabolism: key for the survival of cells detached from the extracellular matrix - Jordan A. Cockfield; Zachary T. Schafer (Molecular & Cellular Oncology, 2021)
Cells that lack attachment to the extracellular matrix (ECM) experience metabolic defects that can lead to caspase-independent cell death. Recently, we discovered that serum and glucocorticoid kinase-1 (SGK1) plays a critical role in the regulation of glucose metabolism, the promotion of energy production, and ultimately the survival of ECM-detached cells. Abbreviations: ECM, extracellular matrix; SGK1, serum and glucocorticoid kinase-1; ROS, reactive oxygen species; CCCP, cyanide m-chlorophenyl hydrazine; PPP, pentose phosphate pathway; G3P, glyceraldhyde-3-phosphate; shRNA, short hairpin RNA; TCA, tricarboxylic acid